Deposition of ultrahard Ti–Si–N coatings by pulsed high-current reactive magnetron sputtering; Technical Physics; Vol. 61, iss. 2 - Oskomov K. V. Konstantin Vladimirovich; Zakharov A. N. Aleksandr Nikolaevich; Rabotkin S. V. Sergey Viktorovich; Soloviev (Solovyev) A. A. Andrey Aleksandrovich (Physical Science Of Materials, 2016)
Title screen